EXPLORING THE IMPACT OF CEO TRAITS ON TAX AVOIDANCE: NARCISSISM, COMPENSATION, AND RISK-TAKING - Karina, Mahda; Prawati, Levana Dhia; Naning Putri Utami; Tiffani Angelica Gunawan (Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2024)
The research aims to investigate the impact of CEO narcissism, CEO compensation, and CEO risk-taking behavior on tax avoidance, while controlling for profitability, leverage, and firm size. This quantitative study utilizes data from companies listed on the Indonesian Stock Exchange over a three-year period. The sample comprises 35 manufacturing companies, totaling 105 observations, selected based on predetermined criteria. Employing a panel data regression model processed with Eviews version 12 software, the analysis examines the relationships between the variables. The findings highlight that CEO compensation, CEO risk-taking behavior, and profitability have a significant positive effect on tax avoidance practices within the sampled firms. However, CEO narcissism, leverage, and firm size do not demonstrate a statistically significant influence on tax avoidance. The positive relationship between CEO compensation and tax avoidance suggests that higher levels of compensation may incentivize CEOs to engage in tax avoidance strategies to maximize personal financial gain. Similarly, CEOs inclined towards risk-taking may be more likely to pursue tax avoidance practices as part of their broader risk-seeking behavior. These findings underscore the importance of considering executive compensation structures and risk management strategies in understanding corporate tax behaviors. Interestingly, the lack of influence of CEO narcissism on tax avoidance contradicts expectations, indicating that narcissistic tendencies among CEOs may not necessarily drive tax avoidance decisions. Moreover, the non-significant effects of leverage and firm size imply that these factors do not directly contribute to tax avoidance behaviors within the context of the sampled manufacturing companies. Overall, this study contributes valuable insights into the determinants of tax avoidance in Indonesian manufacturing firms and provides implications for corporate governance practices and regulatory policies concerning executive compensation and risk management. Further research could delve deeper into the mechanisms underlying these relationships and explore additional factors influencing tax avoidance behaviors.